Hijacking and rewiring of host CircRNA/miRNA/mRNA competitive endogenous RNA (ceRNA) regulatory networks by oncoviruses during development of viral cancers - Kamali, Mohammad Javad; Salehi, Mohammad; Mostafavi, Mehrnaz; Morovatshoar, Reza; Akbari, Mitra; Latifi, Narges; Barzegari, Omid; Ghadimi, Fatemeh; Daraei, Abdolreza (Reviews in medical virology, 2024)
A significant portion of human cancers are caused by oncoviruses (12%–25%). Oncoviruses employ various strategies to promote their replication and induce tumourigenesis in host cells, one of which involves modifying the gene expression patterns of the host cells, leading to the rewiring of genes and resulting in significant changes in cellular processes and signalling pathways. In recent studies, a specific mode of gene regulation known as circular RNA (circRNA)‐mediated competing endogenous RNA (ceRNA) networks has emerged as a key player in this context. CircRNAs, a class of non‐coding RNA molecules, can interact with other RNA molecules, such as mRNAs and microRNAs (miRNAs), through a process known as ceRNA crosstalk. This interaction occurs when circRNAs, acting as sponges, sequester miRNAs, thereby preventing them from binding to their target mRNAs and modulating their expression. By rewiring the host cell genome, oncoviruses have the ability to manipulate the expression and activity of circRNAs, thereby influencing the ceRNA networks that can profoundly impact cellular processes such as cell proliferation, differentiation, apoptosis, and immune responses. This review focuses on a comprehensive evaluation of the latest findings on the involvement of virus‐induced reprogramming of host circRNA‐mediated ceRNA networks in the development and pathophysiology of human viral cancers, including cervical cancer, gastric cancer, nasopharyngeal carcinoma, Kaposi's sarcoma, hepatocellular carcinoma, and diffuse large B cell lymphoma. Understanding these mechanisms can improve our knowledge of how oncoviruses contribute to human tumourigenesis and identify potential targets for developing optimised therapies and diagnostic tools for viral cancers.